P-ed-XRF-geochemical signatures of a 7300 year old Linear Band Pottery house ditch fill at Vráble-Ve'lké Lehemby, Slovakia - House inhabitation and post-depositional processes. (18th May 2017) - Dreibrodt, Stefan; Furholt, Martin; Hofmann, Robert; Hinz, Martin; Cheben, Ivan
Abstract: Over the past decades multi-element analyses have become increasingly important for archaeological and geoarchaeological research. In particular the recent expansion in availability of portable ed-XRF (p-ed-XRF) devices has allowed for the fast acquisition of large data sets. In the presented paper, we evaluate the quantitative measurement capability of a p-ed-XRF device through comparison with wd-XRF. Sampling, drying, and homogenization (sieving < 2 and pulverizing) ensured comparable measurement conditions. The application of He-flotation in the measurement chamber and measurement times of a sufficient duration at low voltage/high amperage conditions increased measurement sensitivity for lighter elements (here at least 90 s at 6 kV, 100 μA), resulting in measurements of a satisfactory quality. In a case study, we measured the elemental contents of the archaeo-sediment-sequence fill of a trench of a ca. 7300 year old Linear Pottery house at the site of Vráble-Ve'lke Lehemby, in southeastern -Slovakia. Based on a model applied at the nearby Bronze Age settlement mound of Fidvár, the P content of the archaeo-sediment was considered as a proxy of palaeo-demography. However, the measured P contents were much too small to reflect the metabolism of a reasonable number of inhabitants. Therefore, in addition to the possibilities of shorter than expected duration of house occupation and incomplete garbage deposition within the ditches, the post-depositional settlement history is considered in detail. Furthermore, bio-cycling by plants during different subsequent phases of Holocene landscape development (forested, agricultural field use) has not been considered extensively in interpretations of the archaeological record so far, but might have had a considerable influence on the shallow buried archaeological record. A reconsideration of the interpretation of the geochemical record from a nearby Bronze Age site (Fidvár) is thus suggested.